solve by substitution. (please show work) x=y x-3y=4 [i know the answer is (-2,2) but idk how to get there]
First, let's find y by substituting x for what x is equal to, so that we will only have one variable and we can solve the equation. x = y Given x - 3y = 4 Given y - 3y = 4 Substitute x for y, because x = y -2y = 4 Subtract y = -2 Divide Now, to find x, we need to substitute our value for y back into the original equation. x = y x = -2 Substitute -2 for y, since y = -2 The correct answer is (-2,-2). Hope this helps!
if x = y then put x where y is or y wherever x is. x-3x=4 -2x = 4 x = -2 now plug that in to find y x-3y = 4 -3y = 4+2 -3y = 6 y = -2